A rapid and low-cost fabrication and integration scheme to render 3D microfluidic architectures for wearable biofluid sampling, manipulation, and sensing. Issue 17 (30th July 2019) - Lin, Haisong; Zhao, Yichao; Lin, Shuyu; Wang, Bo; Yeung, Christopher; Cheng, Xuanbing; Wang, Zhaoqing; Cai, Tianyou; Yu, Wenzhuo; King, Kimber; Tan, Jiawei; Salahi, Kamyar; et al.
Abstract : We devise a simple, scalable, and low-cost "CAD-to-3D Device" fabrication and integration scheme, which renders 3D and complex microfluidic architectures for wearable biofluid sampling, manipulation, and sensing. Abstract : The large-scale deployment of wearable bioanalytical devices for general population longitudinal monitoring necessitates rapid and high throughput manufacturing-amenable fabrication schemes that render disposable, low-cost, and mechanically flexible microfluidic modules capable of performing a variety of bioanalytical operations within a compact footprint. The spatial constraints of previously reported wearable bioanalytical devices (with microfluidic operations confined to 2D), their lack of biofluid manipulation capability, and the complex and low-throughput nature of their fabrication process inherently limit the diversity and frequency of end-point assessments and prevent their deployment at large scale. Here, we devise a simple, scalable, and low-cost "CAD-to-3D Device" fabrication and integration scheme, which renders 3D and complex microfluidic architectures capable of performing biofluid sampling, manipulation, and sensing. The devised scheme is based on laser-cutting of tape-based substrates, which can be programmed at the software-level to rapidly define microfluidic features such as a biofluid collection interface, microchannels, and VIAs (vertical interconnect access), followed by the vertical assembly of pre-patterned layers to realize the final device. To inform the utility of our fabrication scheme, we demonstrated three representative devices to perform sweat collection (with visualizable secretion profile), sample filtration, and simultaneous biofluid actuation and sensing (using a sandwiched-interface). Our devised scheme can be adapted for the fabrication and manufacturing of current and future wearable bioanalytical devices, which in turn will catalyze the large-scale production and deployment of such devices for general population health monitoring.